PENGARUH PEMAKAIAN BENGKUNG TERHADAP NYERI PUNGGUNG PADA IBU NIFAS DI DESA KELING KECAMATAN PARE KABUPATEN KEDIRI - Dewi Taurisiawati Rahayu (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2017)
The postpartum experiences various discomforts during her recovery. Postpartum mother who are in Indonesia, especially in Java, can not be separated from cultural factors in their daily life. One of them is still found many mothers who use bend or stagen after giving birth. Use of this bend is considered to provide many benefits for the recovery process of postpartum mothers. This study aims to determine the effect of the use of bengkung to the incidence of back pain in the puerperal mother. This research uses pre experiment design that is one group pre test-post test design. The research was conducted in Keling Village, Pare District, Kediri Regency. The population in this research is postpartum mother in Keling Village who want to wear bengkung some 20 responden and got sample of 14 respondents. The sampling technique used is purposive sampling. Independent variable in this research is usage of bengkung and dependent variable in this research is back pain. Data analysis technique used is wilcoxon signed rank test. The result of this research showed that the effect of bengkung use on back pain in the puerperal mother (p value = 0,006, CI = 95%). The use of bengkung that are done with safe procedures can help postpartum women to reduce discomfort during health recovery one of them reduce back pain in postpartum.